Semiotic examination of the animal-shaped jade artifacts during the Han Dynasty (206 BC-AD 220) in China - Miao, Su; Perumal, Velu; Md. Yusoff, Irwan Syah; Tualeka, Abdul Rohim (Philosophy Documentation Center, 2024)
During the Han Dynasty (206 BC-AD 220), artisans skillfully shaped jade into figurines inspired by animals, that fostered a profound symbiosis between humanity and the natural world. Notwithstanding the historical appreciation of these artifacts, there exists a lacuna in academic discourse: it does not provide a theoretical framework for using semiotics to analyze animal images of the Han dynasty jade. The present study bridges this gap by integrating semiotic analysis with a historical-cultural approach to probe the generation, communication, and significances of animal symbolisms in the jade craftsmanship of the Han Dynasty. This research has two primary objectives: (1) to analyses the significances of the animal-shaped jade ornaments from this epoch within the Chinese culture, and (2) to elucidate the intricate interplay between humans and animals as depicted through religious, magical, aesthetic, and spiritual dimensions. Our research seeks to decode the narratives and philosophy enshrined in these jade forms, tracing their development within the context of Chinese cosmological thought, philosophical paradigms, state ideologies, and enduring cultural practices. Through this research, we endeavor to demonstrate that animal-shaped jade ornaments serve as key symbols that emerged in ancient China, and these elements collectively sculpted the characters and significance of the animal-shaped jade artifacts of the Han Dynasty.